Association Between Eating Speed and Metabolic Syndrome: A Systematic Review and Meta-Analysis - Yuan, Shu-qian; Liu, Ying-ming; Liang, Wei; Li, Fei-fei; Zeng, Yuan; Liu, Yin-yue; Huang, Shu-zhen; He, Quan-yuan; Quach, Binh; Jiao, Jiao; Baker, Julien S.; Yang, Yi-de (Frontiers in Nutrition, 2021)
Objective: This review aims to systematically summarize and meta-analyze the association between eating speed and metabolic syndrome (MetS). Methods: Following PRISMA guidelines, four electronic databases (PubMed, Web of Science, MEDLINE, and EMBASE) were searched untill March 2021 to identify eligible articles based on a series of inclusion and exclusion criteria. Heterogeneity was examined using I2 statistics. Using random-effects models, the pooled odds ratios (ORs) and 95% confidence intervals (95%CIs) were calculated to evaluate the association between eating speed with MetS and its components, including central obesity, blood pressure (BP), high-density lipoprotein cholesterol (HDL), triglyceride (TG), and fasting plasma glucose (FPG). Results: Of the 10,274 original hits generated by the systematic search, 29 eligible studies with moderate to high quality were included, involving 465155 subjects. The meta-analysis revealed that eating fast was significantly associated with higher risks of MetS (OR=1.54, 95%CI: 1.27-1.86), central obesity (OR=1.54, 95%CI: 1.37-1.73), elevated BP (OR=1.26, 95%CI: 1.13-1.40), low HDL (OR=1.23, 95%CI: 1.15-1.31), elevated TG (OR=1.29, 95%CI: 1.18-1.42), and elevated FPG (OR=1.16, 95%CI: 1.06-1.27) compared to eating slowly. Conclusions: The results of the review indicated that eating speed was significantly associated with MetS and its components. Interventions related to decreasing eating speed may be beneficial for the management of MetS.